Development of a Curriculum to Foster Advancement in Health Science/Health Education. - Savoy, Yolanda; Nelson, Carlin; Tolson, Danita (ABNFF Journal, 2024)
Background: Health disparities, the disproportional distribution of preventable health outcomes among different populations (Bradley & Braham, 2017), require urgent attention within healthcare systems worldwide. These disparities are based on race, ethnicity, socioeconomic status, and geographic location (Agency for Healthcare Research and Quality, 2020). Purpose: Equipping students with the knowledge, skills, and empathy necessary to address health disparities is fundamental to achieving health equity, where everyone has fair access to quality healthcare (American Public Health Association, 2019). By incorporating a holistic approach that connects social factors and health outcomes, future healthcare professionals can become advocates for health equity, a growing focus within healthcare (Lin et al., 2018). Our Approach: Using the Four-Dimensional Framework's emphasis on social justice created by the American Association of Colleges and Universities (2015), our curriculum integrates Social-Emotional Learning (SEL) principles to develop emotional intelligence and build strong relationships with patients. With this framework, educators are empowered to develop, review, or reshape curricula, ensuring adequate preparation of health science students to meet the needs of all populations with their respective communities regionally, nationally, and globally, which is essential to ensuring the provision of safe, quality, evidence-based care (Lee et al., 2013; Steketee et al., 2024). Conclusion: We propose a new undergraduate Health Sciences curriculum based on a four-dimensional framework. This framework combines traditional scientific knowledge with social-emotional learning (SEL) principles, health equity, and inclusion considerations. By revising the curriculum, we empower the next generation of healthcare professionals to become effective advocates for health equity and provide culturally responsive care, giving them a competitive edge in a healthcare landscape that increasingly values these skills.